SOLE, D.B. Inventory of documents - SOLE, D.B. (ARCA, 2018)
Private papers of D.B. Sole, Ambassador Washington and Germany.
COVERAGE Undated; 0,10 Metre.
Keywords: SOLE, D.B.; Inventories; Politicians; National Party